Association between O-GlcNAc levels and platelet function in obese insulin-resistant subjects - Hernández-Huerta, María Teresa; Martínez-Cruz, Ruth; Pérez-Campos Mayoral, Laura; Pina-Canseco, María del Socorro; Solórzano-Mata, Carlos Josué; Martínez-Cruz, Margarito; Vásquez Martínez, Itzel Patricia; Zenteno, Edgar; Laguna Barrios, Luis Ángel; Matias-Cervantes, Carlos Alberto; Pérez-Campos Mayoral, Eduardo; Pérez-Campos, Eduardo (Glycoconjugate journal, 2024)
Obesity is an epidemic associated with platelet and vascular disorders. Platelet O-GlcNAcylation has been poorly studied in obese subjects. We aimed to evaluate O-linked N-acetyl-glucosamine (O-GlcNAc) levels and platelet activity in obese insulin-resistant (ObIR) subjects. Six healthy and six insulin-resistant obese subjects with a body mass index of 22.6 kg/m 2 (SD ± 2.2) and 35.6 kg/m 2 (SD ± 3.8), respectively, were included. Flow cytometry was used to measure markers of platelet activity, expression of P-selectin (CD62P antibody), glycoprotein IIb/IIIa (integrins αIIbβ3 binding to PAC-1 antibody), and thrombin stimulation. O-GlcNAc was determined in the platelets of all test subjects by cytofluometry, intracellular calcium, percentage of platelet aggregation, and immunofluorescence microscopy and Western blot were used to assess O-GlcNAc and OGT (O-GlcNAc transferase) in platelets. Platelets from ObIR subjects had on average 221.4 nM intracellular calcium, 81.89% PAC-1, 22.85% CD62P, 57.48% OGT, and 66.62% O-GlcNAc, while platelets from healthy subjects had on average 719.2 nM intracellular calcium, 4.99% PAC-1, 3.17% CD62P, 18.38% OGT, and 23.41% O-GlcNAc. ObIR subjects showed lower platelet aggregation than healthy subjects, 13.83% and 54%, respectively. The results show that ObIR subjects have increased O-GlcNAc, and increased intraplatelet calcium associated with platelet hyperactivity and compared to healthy subjects, suggesting that changes in platelet protein O-GlcNAcylation and platelet activity might serve as a possible prognostic tool for insulin resistance, prediabetes and its progression to type 2 diabetes mellitus.